PREHAB study: a protocol for a prospective randomised clinical trial of exercise therapy for people living with frailty having cancer surgery. Issue 6 (22nd June 2018) - McIsaac, Daniel I; Saunders, Chelsey; Hladkowicz, Emily; Bryson, Gregory L; Forster, Alan J; Gagne, Sylvain; Huang, Allen; Lalu, Manoj; Lavallee, Luke T; Moloo, Husein; Nantel, Julie; Power, Barbara; et al.
Abstract : Introduction: Exercise prehabilitation may improve outcomes after surgery. Frailty is a key predictor of adverse postoperative outcomes in older people; the multidimensional nature of frailty makes this a population who may derive substantial benefit from exercise prehabilitation. The objective of this trial is to test the efficacy of exercise prehabilitation to improve postoperative functional outcomes for people living with frailty having cancer surgery with curative intent. Methods and analysis: We will conduct a single-centre, parallel-arm randomised controlled trial of home-based exercise prehabilitation versus standard care among consenting patients >60 years having elective cancer surgery (intra-abdominal and intrathoracic) and who are frail (Clinical Frailty Scale >4) . The intervention consists of > 3 weeks of exercise prehabilitation (strength, aerobic and stretching). The primary outcome is the 6 min walk test at the first postoperative clinic visit. Secondary outcomes include the short physical performance battery, health-related quality of life, disability-free survival, complications and health resource utilisation. The primary outcome will be analysed by intention to treat using analysis of covariance. Outcomes up to 1 year after surgery will be ascertained through linkage to administrative data. Ethics and dissemination: Ethical approval has been granted by our ethics review board (Protocol Approval #2016009–01H). Results will be disseminated through presentation at scientific conferences, through peer-reviewed publication, stakeholder organisations and engagement of social and traditional media. Trial registration number: NCT02934230 ; Pre-results.